G11 Prucalopride for treatment refractory constipation in children: a single tertiary centre experience. (12th September 2022) - Motion, Jamie; Barclay, Andrew; Bradnock, Timothy; Fraser, Simon; Allen, Ruth; Walker, Gregor; Flynn, Diana
Abstract : Introduction/Background: Chronic constipation is a common condition in childhood, with an estimated prevalence of 3% worldwide. 1 Commonly no cause is found (idiopathic constipation) although there are a number of important aetiologies to rule out during the evaluation of children with constipation. Pharmacological management is the mainstay of treatment, current NICE recommendations for refractory cases is for referral to surgical services for potentially more invasive therapies. 2 Prucalopride is a 5-HT4 receptor agonist, it produces an enterokinetic effect to increase colonic motility. It is recommended as a treatment of refractory constipation in adult but, despite promise, there is little data supporting its use in paediatrics. 4 Aim: To provide a single tertiary centre experience of using Prucalopride in paediatric patients with treatment refractory constipation. Subjects and Methods: 5 female teenage patients (12–17yrs) average age at initiation 15yrs with treatment refractory constipation in our centre. Patients received a dose of 2mg once daily on an initial 1 month trial of treatment. Table 1 summarises the patient demographics and treatment outcomes. All patients had idiopathic constipation. 4 out of 5 (80%) had rectal biopsies that were normal. 3 out of 5 (60%) had previous transit studies with 2 out of 3 (66%) showing delayed elimination of markers. 1 out of 5 (20%) underwent manometry assessment and this was normal. 2 out of 5 (40%) patients had previous surgical therapy for their constipation with both patients undergoing an ACE procedure and 1 patient additionally receiving anal botox therapy. Results: There was a wide variation in reported stooling prior to commencing Prucalopride and 3 out of 5 (60%) of patients reported an improvement in stooling pattern following the commencement of Prucalopride. In patients where there was an improvement in stooling frequency, all were able to deescalate other medical therapies including reductions in rectal therapies. With regards to adverse side effects: 2 (40%) patients reported pain initially on commencing treatment, 1 (20%) patient reported headache, 1 (20%) patient reported a worsening of existing bladder instability and 1 (20%) patient reported reduction of appetite and weight loss. No patient had adverse side effects that led to the cessation of treatment. Summary: We present our unit's experience in using Prucalopride, a novel agent for use in the management of paediatric constipation. 3 out of 5 patients receiving Prucalopride had an improvement in their stooling pattern with acceptable side effect profiles. Prucalopride should be considered in management of paediatric chronic constipation not responding to conventional medical therapy. References: Tabbers MM, et al . Evaluation and treatment of functional constipation in infants and children: evidence-based recommendations from ESPGHAN and NASPGHAN. J Pediatr Gastroenterol Nutr 2014 Feb;58 (2):258–74. Constipation in children and young people: diagnosis and management Clinical guideline [CG99]Published: 26 May 2010 Last updated: 13 July 2017 NICE. Prucalopride for the treatment of chronic constipation in women Technology appraisal guidance [TA211]Published: 15 December 2010 NICE. Mugie SM, et al . Prucalopride is no more effective than placebo for children with functional constipation. Gastroenterology 2014 Dec;147 (6):1285–95.e1.